Low sodium and tolvaptan have opposite effects in human small cell lung cancer cells. (1st November 2021) - Marroncini, Giada; Anceschi, Cecilia; Naldi, Laura; Fibbi, Benedetta; Baldanzi, Federica; Martinelli, Serena; Polvani, Simone; Maggi, Mario; Peri, Alessandro
Abstract: Purpose: Hyponatraemia is frequently observed in cancer patients and can be due to the syndrome of inappropriate anti-diuresis (SIAD), related to ectopic vasopressin secretion, particularly in small cell lung cancer (SCLC). Hyponatraemia is associated with a worse outcome in cancer patients. The vasopressin receptor antagonist tolvaptan effectively corrects hyponatraemia secondary to SIAD and there is in vitro evidence that it has also an antiproliferative effect in cancer cells. The purpose of this study was i) to analyse the effect of low serum sodium concentrations ([Na + ]) in SCLC cells and ii) to determine whether tolvaptan counteracts tumor progression. Methods: We evaluated cell proliferation, cell cycle, apoptosis, oxidative stress, invasivity in low [Na + ] as well as after exposure to tolvaptan. We also analysed the intracellular signalling pathways involved. Results: In reduced [Na + ] cell proliferation was significantly increased compared to normal [Na + ] and cells were mostly distributed in the G2/M phase. Apoptosis appeared reduced. In addition, the ability to cross matrigel-coated membranes markedly increased. As observed in other cancer cell models, the expression of the heme-oxigenase-1 gene was increased. Finally, we found that in cells cultured in low [Na + ] the RhoA/ROCK1/2 pathway, which is involved in the regulation of actin cytoskeleton, was activated. On the other hand, we found that tolvaptan effectively inhibited cell proliferation, anchorage-independent growth, invasivity and promoted apoptosis. Accordingly, the RhoA/ROCK-1/2 pathway was inhibited. Conclusions: These findings demonstrate for the first time that low [Na + ] favours tumor progression in SCLC cells, whereas tolvaptan effectively inhibits cell proliferation, survival and invasivity.